Sommerlandets udvikling afspejlet i samlingen af arkitekturtegninger i Danmarks Kunstbibliotek: Tegninger, planer, akvareller, fotografier og modeller - Dahlkild, Nan (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2024)
The history of leisure architecture in Denmark is older than the architectural archives. However, the first major leisure gardens and bathing facilities, Klampenborg Vandkuranstalt, from 1845, north of Copenhagen, designed by Gottlieb Bindesbøll, are very well documented in the collection of architectural drawings, which consists of c. 300,000 drawings by Danish architects. The article investigates how the expansion and growing importance of leisure architecture are reflected by the collection: from resorts and summer villas for the upper classes around 1900 to the growing number of holiday cottages of ordinary people, often designed in separated pieces and prefabricated. The collection contains unique drawings by famous Danish architects such as Martin Nyrop, Andreas Clemmensen, Hack Kampmann, P.V. Jensen Klint and Arne Jacobsen, who designed both individual summer houses and the Kubeflex modular system.